Detection of Carotid Webs by CT Angiography, High‐Resolution MRI, and Ultrasound. Issue 1 (28th September 2020) - Zhu, Cuiting; Li, Zhaoxia; Ju, Yi; Zhao, Xingquan
ABSTRACT: BACKGROUND AND PURPOSE: We sought to examine carotid webs (intimal variant fibromuscular dysplasia) by studying their clinical features and imaging profiles. METHODS: All patients ( n = 893) of the Department of Neurology at Beijing Tiantan Hospital between January and December 2019 were retrospectively reviewed for computed tomography angiography (CTA), high‐resolution magnetic resonance imaging (HRMRI), and Doppler ultrasound data. Carotid webs were identified by two experienced neuroimaging experts according to the characteristics of a thin intraluminal filling defect along the posterior wall of the carotid bulb on sagittal CTA and a septum structure in arteries on axial CTA. RESULTS: We found eight carotid web patients by CTA and Doppler ultrasound. Four of eight (50%) carotid webs were observed in the bilateral carotid arteries and other four of eight (50%) were ipsilateral. The mean age of the 8 patients was 50.75 (range 38‐65) years; two were in women. Six of 8 patients (75%) with carotid webs had acute ischemic stroke. Two‐thirds of patients with ischemic stroke were treated with carotid revascularization. Doppler ultrasound indicated that the septum projected into the carotid arteries in all patients. Half of the carotid web patients underwent HRMRI, showing features consistent with CTA findings. The Cohen's kappa coefficient for interobserver agreement in diagnosing carotid webs was .76. CONCLUSIONS: Doppler ultrasound combined with CTA and HRMRI is effective and reliable method to identifying carotid webs, which may be associated with stroke.